Analysis of the MCL-1 gene in Chinese women with idiopathic premature ovarian insufficiency. (3rd September 2021) - Cao, J.; He, Y.; Cai, W.; Zhou, W.; Cong, J.; Tan, R.; Ge, H.; Pu, D.; Wu, J.
Abstract: Objective: Animal studies have demonstrated that myeloid cell leukemia-1 (Mcl-1) gene deficiency leads to premature ovarian failure and decreased reproductive ability in mice. This study investigated the relationship between MCL-1 gene variation and idiopathic premature ovarian insufficiency (POI) in Chinese women. Methods: A total of 200 idiopathic POI patients and 100 healthy controls were recruited for this study, and peripheral blood was collected. First, genomic DNA was extracted from peripheral leukocytes. Then, the entire coding region and splice sites of the MCL-1 gene were amplified by polymerase chain reaction. Chi-squared tests were used to compare the genotype distribution and allele frequency of single nucleotide polymorphisms between the POI and control groups. Results: Three mutations of the MCL-1 gene (c.–36C > T, c.–131C > T and c.78C > T) were identified. After data analysis, c.–36C > T and c.–131C > T in the 5′-untranslated region were both found in the POI group and the control group. No difference was found in the genotype distribution or allelic frequency of either variant between the POI group and the control group ( p > 0.05). The synonymous variant (c.78C > T) in exon 1 was discovered in only one of the control subjects and did not result in a change in amino acid sequence (p.Gly26Gly). Conclusion: MCL-1 gene mutation may not be associated with idiopathic POI in Chinese women.